THE RECONSTRUCTION OF SUFI HADITH EPISTEMOLOGY IN SHAYKH IHSAN JAMPES MANĀHIJ AL-IMDĀD AND ITS RELEVANCE TO THE CONTEMPORARY IDENTITY CRISIS - Muhammad Arwani Rofi'i; Muhammad Chirzin; Asif Trisnani; Nodir Talipov (STAIN Majene, 2026)
This article examines the reconstruction of Sufi hadith epistemology in Manāhij al-Imdād by Syekh Ihsan Jampes and its relevance to the modern identity crisis. The contemporary identity crisis is characterized by fragmentation of the self, disorientation of meaning, and the dominance of instrumental rationality that marginalizes the spiritual dimension of human existence. This study aims to identify the epistemological structure developed by Syekh Ihsan in his Sufi interpretation of hadith and to analyze its contribution in responding to contemporary identity problems. This research employs a qualitative library-based approach with an epistemological and conceptual analysis of Manāhij al-Imdād. The findings reveal that Syekh Ihsan’s Sufi hadith epistemology is integrative in nature, combining bayānī (textual), Burhānī (rational), and ‘irfānī (experiential-spiritual) modes of knowing. Hadith is positioned not merely as a normative source of doctrine but also as a transformative medium for cultivating spiritual consciousness through processes of tazkiyat al-nafs (self-purification), muraqabah (spiritual awareness), and the internalization of the value of ihsan. This epistemological model offers a framework for reconstructing identity that integrates cognitive, ethical, and spiritual dimensions. Accordingly, Syekh Ihsan’s thought contributes theoretically to the development of Sufi hadith studies and presents a relevant conceptual alternative for addressing the modern identity crisis.